The influence of the doctrine of scripture: how beliefs about the Bible affect the way it is read - Hutchinson, Anna (Lexington Books/Fortress Academic, 2024)
"This book analyses how Evangelical Anglicans study the Bible. It explores the relationship between the doctrine of Scripture and hermeneutics as it happens 'on the ground', asking how Bible beliefs influence and affect the interpretative activity and conclusions that Bible readers make"--